1997
DOI: 10.2337/diacare.20.6.978
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Weight Change in Young Adulthood and the Risk of NIDDM: The Sotetsu Study

Abstract: Extreme weight gain between 20 and 25 years of age is a significant predictor of NIDDM, independent of current age, BMI at 20 years of age, and weight change within other age strata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 12 publications
2
19
1
Order By: Relevance
“…Subjects' mean baseline BMI was 31.3 kg/m2, and these people gained an average of 0.1 kg/y (1.0 kg total) over the first 10 years of the study. Two thirds of the sample were women, and the crude incidence of diabetes was 13% (table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects' mean baseline BMI was 31.3 kg/m2, and these people gained an average of 0.1 kg/y (1.0 kg total) over the first 10 years of the study. Two thirds of the sample were women, and the crude incidence of diabetes was 13% (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, two models were defined (table 3). Model I included age, age2 and BMI. The quadratic term for age indicates a non-linear association between age and diabetes risk.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we examined biomarkers related to obesity that may be relevant for the development of Weight change between ages 25 and 40 years W e i g h t c h a n g e b e t w e e n a g e s 4 0 a n d 5 5 y e a r s W e i g h t c h a n g e b e t w e e n a g e s 4 0 a n d chronic diseases, including markers of insulin sensitivity, glucose metabolism, inflammation, dyslipidaemia and hepatic fat accumulation. Several studies have suggested an association between an increase in BMI in adulthood and unfavourable lipid profiles [16][17][18][19] and onset of type 2 diabetes [20][21][22][23][24][25][26][27][28][29][30] as well as cardiovascular diseases after adjustment for attained weight at entry to the study [31][32][33][34][35][36][37]. However, although the association between obesity and risk of various chronic diseases is well documented, there is only limited information about the question of whether the time of onset of obesity or changes in BMI throughout life affects metabolism or disease risk beyond adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…[459][460][461][462][463][464][465] Relative to people who are overweight and do not gain weight, a gain of one kg of weight per year for 10 years in adults who are overweight is associated with a 49% increased risk of developing diabetes in the next 10 years. 464 Weight loss is associated with a substantially reduced risk of diabetes in the general population.…”
Section: Weight Gain and Weight Lossmentioning
confidence: 99%